Effect of adhesive joining on the bending response of alporas foam core sandwich beams - Kirupanandan Palanisamy. (2009)
Cellular solids either in regular lattice or irregular structures such as foams are widely used in light weight transport vehicles, high specific stiff and strength structural designs. These materials compressive response is exploited for designing energy management devices such as helmets, automotive bumpers and blast resistance panels. Good combined properties of high strength, excellent energy absorption and also light weight can be achieved by joining cellular materials with strong and stiff materials to form sandwich panels. Cellular structures can fail in several competing modes based on their constituent material properties and geometries.